Measuring experiences and outcomes of patient safety in primary care: a systematic review of available instruments. - Ricci-Cabello, I; Gonçalves, D; Rojas-García, A; Valderas, J (2014)
BACKGROUND: Despite the enormous potential for adverse events in primary care, the knowledge base about patient safety in this context is still sparse. The lack of appropriate measurement methods is a key factor limiting the development of research in this field. OBJECTIVE: To identify and characterize available patient reported instruments to measure patient safety in primary care. METHODS: We conducted a systematic literature review. We searched in bibliographic sources for empirical studies describing the development, evaluation or use of patient reported instruments assessing patient safety in primary care. Study selection and data extraction were independently conducted by two researchers. RESULTS: We identified 28 studies reporting on 23 different instruments. Fifteen instruments were designed for paper-based self-administration, six for phone interview and two consisted in electronic reporting systems. Most instruments focused on specific aspects of patient safety, most commonly on experiences of adverse drug reactions. Face validity was assessed for 10 instruments (43%), three reported construct validity (13%) and three described reliability (13%). Responsiveness was not ascertained. CONCLUSIONS: Although there is evidence of good psychometric properties for a reduced number of patient reported instruments, currently available instruments do not offer a comprehensive set of resources to measure the effects of interventions to improve patient safety in primary care from a patient perspective. Future research in the field should prioritize (i) the evaluation of the performance of already available instruments and (ii) the development of new instruments that enable an comprehensive assessment of patient safety at general practices.